The Economic effects of standards in Korea - KO, Sangjin (KDI School, 2015)
Since 1960s, Korean national standards have been developed to improve quality of products, ensuring their safety and providing criteria for testing to import and export products. However, there have been few studies on the economic effects of the standards, especially in Korea. This study tries to find the macro economic effects of national standards in Korea by using Cobb-Douglas production function and time-series regression analysis with related factors such as national standards, patents, and imported technology. The result shows that there is statistically significant evidence that increasing national standards have had positive impacts on Korea economic growth from 1970 to 2012 by 0.0589% at a 1% significance level. Considering the industrialization period, from 1970 to 1990, standards had significant positive effects on economic growth in Korea. This statistical analysis indicated that national standards have an important role during the industrialization period, however, patents became more important for economic growth after 1990. Overall, this study shows that standards have been an important role as stimulus for technical progress affecting economic growth during the Korean economic development. And the weight of each factors’ contribution have been changed from standards to patents as the structure of Korean industries have been changed.
Thesis(Master) --KDI School:Master of Public Policy,2015